Limitations and Ambiguities of Colonialism in Guinea-Bissau. Examining the Creole and "Civilized" Space in Colonial Society. (11th December 2015) - Kohl, Christoph
Abstract: This paper is about the exploration of discrepancies between words and deeds of Portuguese colonial rule in Guinea-Bissau, Portugal pretending to "integrate" and "enable" into colonial society those individuals of African origin who were deemed to be "civilized." The essay illustrates potentials and limitations of margins of maneuver of those supposedly subjected under colonial rule. Against this background I will analyze the transformations, continuities, and ruptures of creole identities throughout time, showing how identitarian categories and classifications evolved, changed, and disappeared. It will be shown how the intersection with other identities has been a key characteristic of creole identity over time. In doing so, the analysis focuses on different areas, such as population demographics and classifications, education, and political participation. Résumé: Cet article se penche sur les différences qui existent entre le discours colonial portugais et la réalité de terrain en Guinée-Bissau. Ainsi, la puissance coloniale portugaise prétendait "intégrer" et "habiliter" au sein de la société coloniale les individus d'origine africaine considérés comme étant "civilisés." Ce papier illustre les potentielles marges de manœuvre (ainsi que leurs limites) de ceux qui étaient en théorie des sujets coloniaux. Il propose une analyse des transformations, continuités et ruptures relatives aux identités créoles à travers le temps en montrant comment les catégories d'identité et de classification ont évolué, changé puis disparu. Cet article montre en particulier que l'une des caractéristiques historiques majeures de l'identité créole a été son interaction avec d'autres identités. Pour ce faire, l'analyse se concentre sur l'étude de plusieurs domaines comme la démographie, l'éducation et la participation politique.